Harnessing AI - Ravirajan, Ravi Rajan; Babu, Suresh Chandra (IUP Publications, 2024)
The advent of artificial intelligence marks a new era in agriculture, characterized by intelligent systems capable of learning, adapting, and making autonomous decisions.